Post‐colony swimming migration in the genus Uria - Benjamin Merkel; Hallvard Strøm (Journal of Avian Biology, 2024)
Seabirds within the Alcini subfamily have a unique breeding strategy, with their offspring leaving the colony flightless, at only a quarter of adult body size, accompanied by the father and fledge (become independent) out at sea. In this study we test several hypotheses about this elusive second part of the breeding season, termed swimming migration, for common guillemots Uria aalge and Brünnich's guillemots Uria lomvia by tracking 34 chicks (of which 17 transmitted data) equipped with satellite linked Argos PTTs (Platform Transmitter Terminals) at Bjørnøya, a major colony in the European Arctic. All chicks, presumably accompanied by their fathers, swam actively towards species‐specific autumn staging areas, rather than passively drifted away from the colony with a swim speed generally twice that observed of surrounding surface currents. They swam fastest during the first two days after departure. This coincides with the only time they actively crossed a current and the time needed to leave the area of prey depletion around the colony. They otherwise took advantage of available currents, while still swimming actively during the remainder of their migration towards species‐specific autumn staging areas. These staging areas corresponded to areas used by breeding adults during their moulting period (as confirmed by complementary light‐level logger tracking of adults), rather than being specific nursery areas. Migration duration correlated with distance resulting in species‐specific migration periods that were only a fraction of previously reported fledging periods out at sea, indicating that not only the swimming migration, but also known adult autumn staging regions constitute in effect breeding areas. This work has important implications for our understanding of population dynamics within the Alcini subfamily and the management of these species under multiple threats, while providing the foundation to investigate swimming migrations across their distributional range.